MOLECULAR CHARACTERIZATION OF Alternaria porri (Ellis) Cif., THE CAUSAL AGENT OF PURPLE BLOTCH DISEASE OF ONION, WITH THE HELP OF SIMPLE SEQUENCE REPEAT MARKERS (Applied Biological Research, 2023)
Purple blotch disease of onion, caused by Alternaria porri (Ellis) Cif., causes extensive damage to the bulb and seed crops. The present study was  aimed to assess the morpho-cultural variations and genetic diversity in 14  isolates of A. porri by simple sequence repeat (SSR) markers (selected on  basis of polymorphism pattern). Most isolates showed white fluffy colony growth and yellow to light orange pigmentation with circular, irregular and smooth margin along with clear-cut zonation. During the  study period, 36 loci were obtained and the average expected gene diversity  was found in the range of 0.0531-0.3707. Shan cluster analysis and un weighted pair-group method with arithmetic averages (UPGMA) analysis  revealed that the isolates ‘A.p.B4’ and ‘A.p.B1' had maximum similarity coefficient (0.9166667), while isolates ‘A.p.B12’ and ‘A.p.B13’ had distant  similarity coefficient (0.6111111). The SSR primers D.N.alt4 (200-720 bp) and D.N.alt10 (300-600 bp) represented unique bands for all isolates which  were used for the identification of isolates. The polymorphic information content (PIC) value for primer D.N.alt-4 and D.N.alt-10 was 0.0, with  maximum and minimum PIC value for D.N.alt14 (0.2978) and D.N.alt-50.0495), respectively, thus represented the discriminatory power of a locus.The study revealed that the nine SSR markers tested were helpful in the isolation and molecular characterization of A. porri on the basis of polymorphism or genetic diversity.
Keywords: Alternaria porri; genetic diversity; onion; purple blotch; SSR markers